A novel MHC-II targeted BVDV subunit vaccine induces a neutralizing immunological response in guinea pigs and cattle - Bellido, Demian; Baztarrica, Josefina; Rocha, Lucía Alejandra; Pecora, Andrea; Acosta, Mario; Escribano, José M.; Parreño, Gladys; Wigdorovitz, Andres (Wiley, 2023)
Bovine viral diarrhoea virus (BVDV) is a major cause of economic loss in the cattle industry, worldwide. Infection results in reduced productive performance, growth retardation, reduced milk production and increased susceptibility to other diseases leading to early culling of animals. There are two primary methods used to control the spread of BVDV: the elimination of persistently infected (PI) animals and vaccination. Currently, modified live or inactivated vaccines are used in BVDV vaccination programmes, but there are safety risks or insufficient protection, respectively, with these vaccines. Here, we report the development and efficacy of the first targeted subunit vaccine against BVDV. The core of the vaccine is the fusion of the BVDV structural protein, E2, to a single-chain antibody, APCH, together termed, APCH-E2. The APCH antibody targets the E2 antigen to the major histocompatibility type II molecule (MHC-II) present on antigen-presenting cells. Industrial production of the vaccine is carried out using the baculovirus expression vector system (BEVS) using single-use manufacturing technologies. This new subunit vaccine induces strong BVDV-specific neutralizing antibodies in guinea pigs and cattle. Importantly, in cattle with low levels of natural BVDV-specific neutralizing antibodies, the vaccine induced strong neutralizing antibody levels to above the protective threshold, as determined by a competition ELISA. The APCH-E2 vaccine induced a rapid and sustained neutralizing antibody response compared with a conventional vaccine in cattle.